WAYS OF IMPROVEMENT OF SURGICAL SUTURAL MATERIAL - V. A. Arshakyan; V. E. Gyunter; S. G. Shtofin; P. G. Fedorov; V. A. Samartsev; D. V. Morozov (Acta Biomedica Scientifica, 2017)
According to the research of several authors, titanium nickelide thread has unique properties, which allows it to be considered as a possible basis for suture material. However, for extensive use of titanium nickelide thread in surgical practice, a deeper investigation of its interaction with living tissues is required. In experiments on white rats, we studied the influence of implantation of three types of threads (polypropylene, polyvinylidene fluoride and titanium nickelide) on soft tissues. After 14 days from the moment of implantation, blocks of soft tissue samples with suture material were obtained from animals. The blocks were subjected to microscopic examination, during which the area of the vessels was measured, the degree of fibrosis in the tissue was assessed, and structural changes of the same type were detected. Statistical processing of the received data was carried out with the help of the applied software Statistica 6.0. As a result, it has been established that the implantation of a thread from titanium nickelide, in comparison with other investigated materials, causes less pronounced inflammatory reaction, less edema, less pronounced manifestations of destruction and lymphostasis. This promotes regional angiogenesis, which accelerates the process of restoring soft tissues. The obtained data testify to the prospects of the use of titanium nickelide for the development of a new suture material.